Behavioural Antecedents Complementing Classical Financial Models for Rational Decision Making - Obeng, George (International Journal of Publication and Social Studies, 2019)
Behavioral antecedents precede rational investment decision and an investor cannot achieve rationality without credence to psychological impetus. In literature choice making is rationalized and investors conform to set models and rules which theories has become fundamental and expected to be internalized in portfolio ordering. In the absence of rationality, theory postulates the possibility of financial distress, risk to equity holders, in the event of poor performance when a company geared than optimal fails to honor its debt obligations. The current school of thought suggests cognitive psychology of investors as the factor influencing investment decision disputing the rationality of decisions. Corporate and investment failure to the classical and fundamental theorist is alluded to irrational decision and to the behaviorist it is not a rationality issue but cognitive psychological filters that influence the investment decision. Information, its source and influence is out of the equation, as a stimuli. Literature is synthesized on the investment decisions from traditional and classical financial models and how independent of behavioral psychological impinges. Attention is directed to the fact that investors react differently to available information, with rationality achieved when psychological impinges complement classical models, according to investors understanding, disposition, expectations and self-interest.